Систематический статус и географическая изменчивость славки белоусой (Sylvia mystacea Мёnёtr.) - Казаков, Б.А. (Вестник зоологии, 1973)
On the basis of collection data processing it was established that within the boundaries of the species areal there exists a considerable geographical variability. Three geographical races are distinguished. S. m. mystacea Men e t r i e s inhabits the Kura-river area and western coast of the Caspian sea, S. In. rubescens B1 a n f or d— the valleys of the Tigris and Euphrates rivers, S. m. turcmenica Z a r u d n y i et. Bilke
vitsch— the valleys of the Amu Darya, Syr Daria, Tedjen and Murhab rivers. Subspecies are well distinguished in colour and size.
As opposed to some authors (Portenko, 1960) the status of the species is suggested to be preserved for S. mystaceae.